Anarsioses, a new generic name for Phyllonorycter aberrans (Braun) (Lepidoptera: Gracillariidae) - Davis, Donald R. (Zootaxa, 2019)
Annette Braun (1930) described the leafmining moth Phyllonorycter aberrans in the genus Lithocolletis Hübner, 1825. The species was later transferred to Phyllonorycter by Davis (1983). Recent morphological studies on North American Gracillariidae by the author have shown that P. aberrans requires a new generic placement. Generic distinction was also recognized by the molecular studies of Kawahara et al. (2017: fig. 2). Anarsioses is very similar to Phyllonorycter in general head morphology and wing venation, but differs in the unusual asymmetry of the male genitalia and in larval biology.